Controle postural e Doença de Alzheimer: efeitos de diferentes condições de dupla tarefa e de um programa de exercícios físicos domiciliares - Costa, Danielle Chagas Pereira da Silva (2025)
This doctoral thesis comprises two studies focusing on the assessment and intervention of postural control, dual-task performance, and Alzheimer's disease (AD). Study I: The first study aimed to investigate the effects of different dual-task conditions on postural control during the sit-to-stand transition in older adults with mild to moderate AD. This cross-sectional study included 24 older adults diagnosed with AD (8 men and 16 women, mean age 77.9±6.3 years). Participants were assessed under four conditions using a force platform: (i) single-task, (ii) bimanual motor dual-task, (iii) unimanual motor dual-task (dominant and non-dominant), and (iv) cognitive dual-task, across the three phases of the sit-to-stand movement. Postural control variables—Center of Pressure (CoP) Area, Anteroposterior and Mediolateral Amplitude, and Velocity—were analyzed. Cognitive functions were assessed using the Frontal Assessment Battery and the Addenbrooke’s Cognitive Examination. Functional physical performance was evaluated using the Five-Times Sit-to-Stand Test. A force platform (BERTEC 400, EMG System do Brasil®) was used to analyze postural control. Data were analyzed using one-way ANOVA. Our hypothesis was partially confirmed: a significant difference was observed in Anteroposterior Amplitude during phase 2 of the sit-to-stand transition, specifically between the single-task condition and the dominant unimanual motor dual-task condition. This finding suggests that asymmetric upper limb use has a more pronounced impact on postural control. These results highlight the need to incorporate asymmetric motor tasks in rehabilitation, as they pose greater challenges to postural control in older adults with AD, regardless of disease stage, and may enhance therapeutic strategies for this population. Study II: The second study evaluated the effects of a home-based physical exercise program (AD-HOMEX) on postural control in older adults with AD during the sit-to-stand task under dual-task conditions. This was a randomized controlled clinical trial with 25 participants, randomly allocated to the Intervention Group (IG) (n=13, mean age 79.5±0.4 years) and the Control Group (CG) (n=12, mean age 76±0.5 years). The AD-HOMEX program included multimodal exercises (stretching, strength, balance, and dual-task training) performed three times per week over 16 weeks. Postural control was assessed before (M1) and after the intervention (M2) using the BERTEC 400 force platform. The assessed conditions were the same as in Study I, with CoP Area as the primary variable of interest. The sit-to-stand movement was subdivided into three phases. Group (IG vs. CG) and time (M1 vs. M2) interactions were tested using mixed linear models with interactions (MANOVA). Despite high adherence to the program (81.25%) and session attendance (92.3%), no significant differences in postural control were observed between groups or time points under any dual-task condition. Although AD-HOMEX was a structured multimodal exercise program incorporating dual-task stimuli, it was not sufficient to improve postural control during the sit-to-stand task under various dual-task complexities. These findings suggest that home-based interventions should include more specific functional training for the sit-to-stand task under dual-task conditions to optimize postural control in challenging situations. Furthermore, both studies employed refined methodologies to assess postural control in dynamic and ecologically valid contexts, advancing the understanding of postural control mechanisms in AD. The findings provide valuable insights for improving rehabilitation strategies and fall prevention, reinforcing the need for more targeted approaches for this population.